Chemical Composition of Essential Oils from the Leaves of Syzygium Bullockii and Syzygium Tsoongii in Ke Go Nature Reserve, Ha Tinh Province - Hau Khanh, Tran; Ban, Pham Hong; Hoi, Tran Minh (VNU Journal of Science: Natural Sciences and Technology, 2021)
Chemical composition of essential oils obtained from the leaf of Syzygium bullockii and Syzygium tsoongii were reported, corresponding oil content 0,36% and 0,27%. The analysis was performed by means of gas chromatography-flame ionization detector (GC-FID) and gas chromatography coupled with mass spectrometry (GC-MS). Twenty-seven components were identified in leaf oil of Syzygium bullockii, which represented about 76,75% of the total composition of the oil and six components were not identified, which represented 15,72%. The major constituents of the essential oil were (E)-caryophyllene (49,65%), spathulenol (4,29%), caryophyllene oxide (4,14%), bicyclogermacrene (3,35%), 2-tridecanone (3,25%). Fourty-six components were identified in leaf oil of Syzygium tsoongii, which presented about 99.71% of the total composition of the oil. The major constituents of the essential oil were E-caryophyllene (23,40%), bicyclogermacrene (21,23%), (Z)-β-ocimene (10,61%), α-humulene (6,33%), (E)-β-ocimene (4,99%). For the first time, the chemical compositions of the essential oils of Syzygium bullockii and Syzygium tsoongii from Vietnam were being reported.